The Prospect of the Internet of Renewable Energy (IoRE) in Electricity Networks - Igbinovia, Famous Oghomwen; Křupka, Jiří (IEEE (Institute of Electrical and Electronics Engineers), 2019)
There is a global drive towards a complete renewable electricity system. A purely renewable electricity system with the Internet of Renewable Energy (IoRE) is a promising solution for providing efficient, reliable and comprehensive environmentally friendly services to electricity consumers. The internet technology is fundamental in the architecture of an Internet of Renewable Energy (IoRE) system. This paper proposes an Internet of Renewable Energy platform for electricity networks. The concept of IoRE has been introduced for a pollution free electricity grid architecture, which will bring about a total environmentally friendly electricity grid.
Možnosti internetu obnovitelné energie v elektrických sítích
Keywords: Industrial internet of things; internet of energy; internet of renewable energy; internet of things; network architecture; renewable energy; Průmyslový internet věcí; internet energie; internet obnovitelné energie; Internet věcí; síťová architektura; obnovitelná energie